2019
DOI: 10.1016/j.contraception.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

One-year continuation of postpartum intrauterine contraceptive device: findings from a retrospective cohort study in India

Abstract: Objective To evaluate outcomes of a national postpartum (within 48 h of delivery) copper intrauterine device placement (PPCuIUD) program in six “high-focus states” with high unmet family planning need in India. Study design We identified high-volume district hospitals that provided PPCuIUD in six (Bihar, Jharkhand, Uttar Pradesh, Uttarakhand, Madhya Pradesh and Chhattisgarh) Indian states (two per state). Each selected hospital maintained a list of PPCuIUD acceptors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
6
13
0
1
Order By: Relevance
“…Method continuation in the current study was found to be high (86%) at one year of follow-up which is comparable or better than the 55-82% commonly reported by many other published studies [3,20,[27][28][29][30][31]. Moreover, the most vulnerable period for PPIUD discontinuation was that period after the puerperium to six months of delivery (i.e., 43-180 days) contrary to the period of up to 6 weeks post-delivery that is reported to be critical for IUD related complications and removal in some earlier studies [32,33].…”
Section: Discussionsupporting
confidence: 82%
“…Method continuation in the current study was found to be high (86%) at one year of follow-up which is comparable or better than the 55-82% commonly reported by many other published studies [3,20,[27][28][29][30][31]. Moreover, the most vulnerable period for PPIUD discontinuation was that period after the puerperium to six months of delivery (i.e., 43-180 days) contrary to the period of up to 6 weeks post-delivery that is reported to be critical for IUD related complications and removal in some earlier studies [32,33].…”
Section: Discussionsupporting
confidence: 82%
“…Other in uences of discontinuation were abdominal pain, IUD expulsion, and voluntary IUD removal in order to allow pregnancy. Generally, the overall spectrum of complications attributable to PPIUD discontinuation in current study is similar to what is commonly reported by others [20,30].…”
Section: Discussionsupporting
confidence: 90%
“…Three quarters of the women who discontinued the IUD resorted to Calendar and condom methods which are among the least effective compared to other available modern methods of contraception. Non-use of an effective method after PPIUD discontinuation has been reported by others where up to half of clients did not use an alternative method [30]. This phenomenon could be a re ection of negative attitude towards modern contraception in general rather than being speci c to the IUD, thus, calling for the need to intensify education on postpartum contraception and family planning in general.…”
Section: Discussionmentioning
confidence: 94%
“…Assim, devido ao baixo número de inserções imediatas, não se mostrou relevante comparar as taxas de expulsão entre os dispositivos inseridos no puerpério imediato e precoce. Deve-se ressaltar que uma inserção no puerpério imediato traz como benefício uma maior taxa de adesão e de continuidade de uso do método (17,29) , bem como reduz o número de gravidez indesejada e aumenta o intervalo entre os filhos (22) .…”
Section: Discussionunclassified